(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Title: The Creation of Indigenousness as Poetic-Hermaneutic Operation in Lope de Vega’s Auraco Tamed In Lope de Vega’s Auraco Tamed, dramaturgical composition generates an apologetic structure between the conqueror and the conquered, the symbolic germination of which serves as mirror where the indigenous body is recreated and resignified as a messianic figure. The conversion’s mise en scène constructs a liminal, hermaneutic device where the indigenous body passes through the body of Christ, reconverting the epistemic violence of death by impalement into the symbol of the martyred cross. The scene reveals the illumination of a saving logos that radiates through all expectation, like virtue and obligation that are rebirthed through the history of conquered blood. The body of Caupolicán is imagotype staging the cleavage of authority and power, inscribing conflict in the culture of conquered blood, reedified as communion in the conscious word.